Spinal Canal Involvement in Solitary Infantile Myofibromatosis: Case Report - Gautam, S.N.; Mittal, Siddharth (Indian Journal of Neurosurgery, 2017)
Infantile myofibromatosis involving the spinal canal is very rare; only 11 cases have been reported so far in the literature. The authors present a case of an 18-month-old male child who presented with the history of dribbling of urine and weakness in bilateral lower limbs since 2 months. MRI of spine revealed single intramedullary intradural space-occupying lesion (SOL) at D1 to D2.The patient underwent laminectomy with excision of SOL with biopsy report suggestive of benign nerve sheath tumor, and immunohistochemistry report revealed desmin negative, smooth muscle actin positive, and S-100 focally positive infantile myofibromatosis. The patient gradually recovered and had a clear stream of urine with improved movements and tone of bilateral lower limbs at the time of discharge.
Keywords: solitary infantile myofibromatosis; spinal canal; intramedullary